BS1 Adipose tissue derived ceramides regulate myocardial redox state and predict cardiovascular outcomes. (6th June 2022) - Polkinghorne, Murray; Akawi, Nadia; Badi, Ileana; Checa, Antonio; Kotanidis, Christos; Akoumianakis, Ioannis; Antonopoulos, Alexios; Krasopoulos, George; Sayeed, Rana; Walcot, Nicholas; Channon, Keith M; Wheelock, Craig; et al.
Abstract : Background: Obesity is linked to both dysfunctional adipose tissue (AT) and heart failure, but the exact mechanisms mediating these associations are unknown. Although ceramides biosynthesis is dysregulated in obesity, their role as mediators of obesity-induced myocardial dysfunction is unclear. Purpose: We investigate the causal role of AT-derived ceramides in the regulation of myocardial redox state and explore their role in predicting cardiovascular outcomes. Methods: The study population included a total of 880 patients undergoing cardiac surgery. A panel of 20 sphingolipids was measured in plasma as well as in biopsies of subcutaneous AT (ScAT), thoracic AT (ThAT) and epicardial AT (EpAT) and their secretome, obtained from a subgroup of n=48. Myocardial redox state was measured using lucigenin chemiluminescence and the contribution of NOXs, uncoupled nitric oxide synthases and mitochondrial oxidases in O2.- production was quantified. The cohort was followed up for a median of 8.3 years. Genome-wide genetic analysis was done using the UK Biobank array. A total of 99, 524 SNPs within 50kb of 110 genes involved in sphingolipid biosynthesis were analysed to identify genetic variants that could predict CVD outcomes using cis-Mendelian Randomisation. The underlying mechanisms were then explored further, using differentiated H9c2 cardiomyocytes in vitro and human right atrial tissue ex vivo. Results: The production and secretion of C16:0-ceramide (CerC16) was higher in visceral AT (EpAT and ThAT) compared to ScAT (p<0.0001). Patients with high plasma levels of CerC16 and its derivative C16:0-glucosylceramide (GlcC16) had higher myocardial O2.- production vs those with low/int. levels (p<0.05 for both) (A). To test the causality of this association, we performed a targeted single-SNP analysis for the genetic prediction of GlcC16 levels demonstrating that rs112572487, an intronic variant in UGCG (an enzyme that catalyses glucosylceramide formation from ceramides), was the top hit (B). Indeed, those with the rs112572487 minor allele (G) displayed significantly increased myocardial NOX-derived O2.- (C) and plasma GlcC16 levels (D) vs those without. Exogenous CerC16 (20nM) induced NOX-derived O2.- production in H9c2 cardiomyocytes, an effect prevented by the UGCG inhibitor D-PDMP (E), suggesting that GlcC16 is a modifiable regulator of myocardial NOX-O2.-. Importantly, high plasma GlcC16 levels were associated with a higher risk of cardiac death and/or heart failure (adj. HR=2.128 [95%CI: 1.101, 4.115], p=0.025, for high vs low/int. levels), a relationship also seen with rs112572487 (F). Conclusions: We demonstrate for the first time, that AT-derived ceramides are causally related with dysregulated myocardial redox signalling and adverse cardiovascular disease outcomes in patients with advanced atherosclerosis. As such, GlcC16 may be an important therapeutic target for the prevention and treatment of cardiovascular complications in obesity and diabetes.